Pesantren Revitalization as an Effort to Prevent Brain Rot in the Young Generation: A Neurological Approach - Wildan Fahdika Ahmad (Journal of Islamic Studies and Civilization, 2024)
The digital era that triggers excessive social media consumption has given rise to a non-medical term called "brain rot" as named by Oxford as Word of the Year 2024. Of the various writings on the brain rot phenomenon, there are still very few that offer steps to anticipate this phenomenon from occurring in the young generation of Indonesia. This study aims to offer a perspective on "revitalizing Islamic boarding schools" as an effort to overcome this problem. The method used is the "qualitative grounded theory" method. This study utilizes a neurological approach to explain the relationship between the brain rot phenomenon and the revitalization of Islamic boarding schools. The research data were obtained through literature studies, which were taken from data sources in the form of writings or statements by experts regarding Islamic boarding schools, Islamic boarding school revitalization, neurology, and brain rot. The data that was successfully collected was then analyzed with the following stages: data reduction, data presentation, verification with a neurological approach.